The Role of Calcium‐Sensing Receptors in Endothelin‐1‐Dependent Effects on Adult Rat Ventricular Cardiomyocytes: Possible Contribution to Adaptive Myocardial Hypertrophy. Issue 9 (10th April 2017) - Dyukova, Elena; Schreckenberg, Rolf; Arens, Christoph; Sitdikova, Guzel; Schlüter, Klaus‐Dieter
Abstract : Nitric oxide (NO)‐deficiency as it occurs during endothelial dysfunction activates the endothelin‐1 (ET‐1) system and increases the expression of receptor activity modifying protein (RAMP)‐1 that acts as a chaperon for calcium‐sensing receptors (CaR) that have recently been identified to improve cardiac function. Here, we hypothesized that ET‐1 increases the cardiac expression of CaR and thereby induces an adaptive type of hypertrophy. Expressions of RAMP‐1, endothelin receptors, and CaR were analyzed by RT‐PCR in left ventricular tissues of L‐NAME‐treated rats. Effects of ET‐1 on CaR expression and cell function (load free cell shortening) were analyzed in adult rat ventricular cardiomyocytes. siRNA directed against CaR and RAMP‐1 was used to investigate a causal relationship. PD142893 and BQ788 were used to dissect the contribution of ETB1, ETB2, and ETA receptors. Non‐specific NO synthase inhibition with L‐Nitro arginine methyl ester (L‐NAME) caused a cardiac upregulation of ETB receptors and CaR suggesting a paracrine effect of ET‐1 on cardiomyocytes. Indeed, ET‐1 induced the expression of CaR in cultured cardiomyocytes. Under these conditions, cardiomyocytes increased cell size (hypertrophy) but maintained normal function. Inhibition of ETA and ETB1 receptors led to ET‐1‐dependent reduction in cell shortening and attenuated up‐regulation of CaR. Down‐regulation of RAMP‐1 reduced CaR responsiveness. In conclusion, ET‐1 causes an adaptive type of hypertrophy by up‐regulation of CaR in cardiomyocytes via ETA and/or ETB1 receptors. J. Cell. Physiol. 232: 2508–2518, 2017. © 2016 Wiley Periodicals, Inc. Abstract : Current manuscript is the first report indicating the ET‐1‐dependent upregulation of CaR receptor in cardiomyocytes and it shows that this upregulation allows cardiac cells to maintain proper function. Second new finding indicates involvement of ETA and /or ETB1 receptors in adaptive hypertrophy in cardiomyocytes, whereas ETB2 receptors activation leads to mal‐adaptive effect. Finally, chaperone activity of RAMP1 is required for the functional coupling of CaR in cardiomyocytes.